(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Emergency situations in schools require students to be adequately prepared to provide first aid. In such circumstances, individuals are expected to be ready and capable of delivering appropriate initial care. Adolescents aged 15–24 years constitute a population that is particularly vulnerable to accidents, with common emergency conditions including injuries, wounds, and trauma. First aid refers to the immediate assistance provided to individuals experiencing sudden illness or injury prior to receiving advanced medical treatment at healthcare facilities such as clinics or hospitals. The primary objectives of first aid are to save lives, prevent disability, provide comfort, and support the recovery process. However, one of the main challenges in emergency response is the limited knowledge and practical skills of first aid providers.This condition highlights the importance of basic medical first aid training for senior high school students, not only to improve knowledge but also to enhance practical competencies in managing emergency situations. Accordingly, a bandaging and splinting training program was conducted at SMA Santo Paulus Jakarta. The activity involved 58 students from grades X and XI who participated in interactive educational sessions, hands-on simulations, and evaluations using pre-test and post-test instruments. Statistical analysis using the Wilcoxon test demonstrated a significant increase in knowledge scores after the training (p < 0.001), with a participation rate of 86.2% of the target population. Moreover, most participants were able to correctly demonstrate bandaging and splinting techniques. Overall, the training effectively improved students’ knowledge and practical skills, strengthening emergency preparedness and promoting appropriate first aid responses. Keywords: Splinting, Health Education, High School Students. Keadaan darurat di sekolah menuntut kesiapsiagaan siswa dalam memberikan pertolongan pertama. Dalam situasi tersebut, setiap individu dituntut untuk siap dan mampu memberikan penanganan awal yang tepat. Kelompok usia 15–24 tahun, khususnya remaja, merupakan populasi yang rentan mengalami kecelakaan, kondisi darurat yang sering terjadi pada kelompok usia ini antara lain kecelakaan, luka, dan cedera. Pertolongan pertama merupakan tindakan segera yang diberikan kepada seseorang yang mengalami sakit mendadak atau cedera akibat kecelakaan sebelum memperoleh penanganan medis lanjutan di fasilitas kesehatan seperti di klinik ataupun rumah sakit. Pertolongan pertama mempunyai tujuan adalah untuk menyelamatkan nyawa, mencegah terjadinya kecacatan, memberikan rasa nyaman, serta mendukung proses penyembuhan, namun salah satu kendala utama dalam menyelamatkan korban pada kondisi darurat adalah terbatasnya pengetahuan dan keterampilan pertolongan pertama pada penolong korban. Kondisi ini menunjukkan bahwa pemberian pelatihan pertolongan pertama medis dasar bagi siswa Sekolah Menengah Atas menjadi sangat penting, tidak hanya untuk meningkatkan pengetahuan tetapi juga keterampilan praktis dalam menghadapi keadaan darurat. Untuk itu, dilakukan pelatihan balut bidai di SMA Santo Paulus Jakarta. Kegiatan melibatkan 58 siswa kelas X dan XI yang mengikuti penyuluhan interaktif, simulasi praktik, serta evaluasi melalui pre-test dan post-test. Analisis dengan uji Wilcoxon menunjukkan peningkatan signifikan skor pengetahuan setelah pelatihan (p < 0,001), dengan cakupan partisipasi 86,2% dari total sasaran. Mayoritas peserta juga mampu memperagakan keterampilan praktis dengan benar. Kesimpulan: Penyuluhan dan pelatihan ini berhasil mencapai tujuan, terbukti efektif meningkatkan pengetahuan dan keterampilan siswa dalam balut bidai. Kata Kunci: Balut Bidai, Pendidikan Kesehatan, Siswa Sekolah Menengah.